Spectroscopic and metal binding properties of a de novo metalloprotein binding a tetrazinc cluster. Issue 10 (11th September 2018) - Chino, Marco; Zhang, Shao‐Qing; Pirro, Fabio; Leone, Linda; Maglio, Ornella; Lombardi, Angela; DeGrado, William F.
Abstract: De novo design provides an attractive approach, which allows one to test and refine the principles guiding metalloproteins in defining the geometry and reactivity of their metal ion cofactors. Although impressive progress has been made in designing proteins that bind transition metal ions including iron–sulfur clusters, the design of tetranuclear clusters with oxygen‐rich environments remains in its infancy. In previous work, we described the design of homotetrameric four‐helix bundles that bind tetra‐Zn 2+ clusters. The crystal structures of the helical proteins were in good agreement with the overall design, and the metal‐binding and conformational properties of the helical bundles in solution were consistent with the crystal structures. However, the corresponding apo ‐proteins were not fully folded in solution. In this work, we design three peptides, based on the crystal structure of the original bundles. One of the peptides forms tetramers in aqueous solution in the absence of metal ions as assessed by CD and NMR. It also binds Zn 2+ in the intended stoichiometry. These studies strongly suggest that the desired structure has been achieved in the apo state, providing evidence that the peptide is able to actively impart the designed geometry to the metal cluster. Abstract :